¿Adoptados por Jesucristo?: Examen de algunos textos agustinianos - Luis Vizcaíno, Pío de (Estudio agustiniano, 2025)
Call no one your Father on earth, for you have only one Father in heaven (Mt 23,9). Given this categorical affirmation, how does St. Augustine that the Bridegroom, that is, JesusChrist have Children (Mt 9,15: The Children of the Bridegroom), of whom he should consequently be called father? The first part of the study tries to anserw this question, which excludes speaking of a filiation by adoption and proposes a "natural"-spiritual. filiation. The second part does the same with two questions raised by the saint's use of the concept of adoption: how can it be explained that in several texts he affirms that JesusChrist adopted his servants as sons -which would make him and (adoptive) father,- and in others that he adopted them as brothers -if all adoptions is only os sons-? The anserw excludes any filial adoption by Christ and highlights the importance given to the mediation of Jesus Christ in the adoption by God the Father.